Genetic linkage map construction for white jute (Corchorus capsularis L.) using SRAP, ISSR and RAPD markers. Issue 6 (11th July 2014) - Chen, Yanping; Zhang, Liwu; Qi, Jianmin; Chen, Hui; Tao, Aifen; Xu, Jiantang; Lin, Lihui; Fan, Pingping; Flachowsky, H.
Abstract White jute (Corchorus capsularis) and dark jute (Corchorus olitorius) are two important cultivated crops that are used for natural fibre production. Some genetic maps have been developed for dark jute, but the genetic map information for white jute (C. capsularis) is limited. In this study, a linkage map comprising 44 sequence‐related amplified polymorphisms (SRAPs), 57 intersimple sequence repeats (ISSRs) and 18 randomly amplified polymorphic DNA (RAPD) covering 2185.7 cM with a mean density of 18.7 cM per locus was constructed in an F2 population consisting of 185 individuals derived from a cross between two diverse genotypes of 'Xinxuan No. 1' and 'Qiongyueqing' in white jute. These markers were evenly distributed in the linkage groups without any clustering. This genetic linkage map construction will facilitate the mapping of agronomic traits and marker‐assisted selection breeding in white jute.